Dampak Kebocoran Data Bjorka pada Kepatuhan Wajib Pajak: Perspektif Akuntansi Keperilakuan - Muh. Akbar Fhad Syahril; Hamida Hasan; Nurhaedah Hasan (Jurnal Litigasi Amsir, 2024)
This study examines the impact of NPWP data leakage by Bjorka on the perception of security and compliance of taxpayers in Indonesia from the perspective of behavioral accounting. Using normative legal research methods with legislative, conceptual, and case approaches, this study analyzes how the incident affects public trust in the tax system. The results show that data leaks have the potential to reduce tax compliance levels through the erosion of trust and changes in security perceptions. Behavioral accounting theories such as attribution theory, planned behavior, and procedural fairness are used to explain this phenomenon. The study also proposes a comprehensive mitigation strategy that includes improved technical security, communication reforms, and restructuring of tax compliance incentives. The implications of this study are significant for policymakers in designing strategies to restore public trust and improve tax compliance after data leak incidents.